Financial Planning and Investment Decision Strategy among the IT Women Professionals - B. Padmaja; C. Kathiravan (International Journal of Psychosocial Rehabilitation, 2019)
India Women’s contributions to the family, business, and society are now being acknowledged in financial planning. When the career paths of contemporary women in the information technology sector. The purpose of this study is to demonstrate the circumstances that lead a female employee to take a career hiatus. The purpose of this study is to shed light on the career advancement of female employees in the information technology sector. Women’s participation in economic activities is increasing, as is their role in investment decisions. Her voice in investing decisions is growing more prominent as a result of her increased education, work, and financial contributions to the family. When it comes to investing, the role of a woman’s husband becomes critical. The purpose of this study is to ascertain the relationship and influence of Financial Planning and Investment Decision Strategy on Hydrabad’s IT Women Professionals. Financial Planning serves as the independent variable for this purpose, while its sub variables include cash and money management, insurance preparation, investment planning, and tax preparation. Investment Decision Strategy is a dependent variable, and its sub variables include Rational, Intuitive, Dependent, Avoidant, and Spontaneous. This study is descriptive in nature, and data will be collected using a questionnaire distributed to 409 employees of Hydrabad’s IT Women Professionals. Multiple regression analysis will be employed to conduct the analysis in this study. We concluded from the outcomes of this study that there is a favourable association and a significant influence on the financial planning and investment strategy of IT women employees in Hyderabad.